Dispersion and testing of single-walled carbon nanotubes - Ang, Mei Ping (2010)
Carbon nanotubes (CNTs) possess exceptional mechanical, thermal and electrical properties. They are thermally stable up to 2800oC in vacuum and have thermal conductivity about twice as high as diamond. They exhibit electric current carrying capacity 1000 times higher than copper wires.